Introduction of integration / Aishah binti Mahat - Mahat, Aishah (Universiti Teknologi MARA, Johor Kampus Pasir Gudang, 2023)
This e-book, Introduction of Integration aimed to help students in Calculus subject. Targeted users for this module is students who take Calculus course. This e-books is divided into four subtopics which includes Integration by Part, Integration of Trigonometric Functions, Integration of Substitutions, and Integration of Rational Functions. All the four topics above will be completed in accordance to lesson planned. Mathematical tips and formulas will be displayed based on the syllabus carried out during the lesson. At the end of each topic, targeted students should meet up with the lecturer to discuss over the solution of Calculus problem. With the existence of this e-book, hopefully it will be beneficial and give positive impact towards teaching and learning for students and lecturers as a whole.